Rational design of cobalt sulfide anchored on nitrogen-doped carbon derived from cyanobacteria waste enables efficient activation of peroxymonosulfate for organic pollutants oxidation. (February 2023) - Wang, Ronghan; He, Zixiang; Wang, Wenjun; Bu, Jiaqi; Wang, Dongbo; Zeng, Guangming; Zhou, Chengyun; Xiong, Weiping; Yang, Yang
Abstract: With the increasing of eutrophication in water body, algae blooms have become one of the global environmental problems. The cyanobacteria waste has placed a severe burden on the environment and transforming cyanobacteria into functional materials may be a wise approach. Herein, cobaltous sulfide/nitrogen-doped biochar (N-BC/CoSx ) composite was synthesized by pyrolysis of cyanobacteria waste. The N-BC/CoSx showed excellent performance in peroxymonosulfate (PMS) activation for enrofloxacin (ENR) degradation, which could remove more than 90% ENR within 60 min. The influencing factors of pH and catalyst dosage on ENR removal efficiency were studied. The N-BC/CoSx showed good recyclability in the cycle runs. The radicals (O2 -, OH andSO4 - ) and the non-radical species (charge transfer and 1 O2 ) were generated in the ENR degradation. The cycle of Co(II)/Co(III) m ay contribute to the radical generation process. This work proved that metal sulfide modified cyanobacteria biochar has a specific application value in water pollution control and provides a new method for resource utilization of cyanobacteria . Graphical abstract: Image 1 Highlights: N-BC/CoSx was achieved by the reuse of cyanobacteria waste. 99% of ENR was removed within 60 min in N-BC/CoSx/PMS system. Both radical and non-radical processes contributed to the oxidation reaction. N-BC/CoSx/PMS system exhibited great potential in practical application.